2018
DOI: 10.13005/bpj/1438
|View full text |Cite
|
Sign up to set email alerts
|

Centella Asiatica Increased the Body Length Through the Modulation of Antioxidant in Rotenone-Induced Zebrafish Larvae

Abstract: Centella asiatica (CA) is herbal medicine that used as traditional medicine including ayurvedic theraphy since hundreds years ago. This herb containa of pentacyclic triterpenoids such as asiaticoside, madecassoside, Asiatic acid and brahmoside that proved had anti-oxidant and anti-inflammatory properties. This research aims to know the effect of ethanolic extract of CA extract against the length of rotenone-induced zebrafish larvae through the free radicals.mechanism. This research used zebrafish larvae unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It makes the angiogenesis running normally that impacted to the escalation of body length [13]. The administration of Centella asiatica has proven in the enhancement of rotenone induced zebrafish body length through the elevation of BDNF, BAX, Hsp60 and SOD also decrease MDA [30][31]45].…”
Section: Resultsmentioning
confidence: 99%
“…It makes the angiogenesis running normally that impacted to the escalation of body length [13]. The administration of Centella asiatica has proven in the enhancement of rotenone induced zebrafish body length through the elevation of BDNF, BAX, Hsp60 and SOD also decrease MDA [30][31]45].…”
Section: Resultsmentioning
confidence: 99%
“…The ingredients of EM used with 10 times concentration is 0,815 gr MgSO4, 0.25 gr CaCl2, 0,15 gr KCl and 5 gr NaCl, diluted in 500 mL of aquadest. 23 Cinnamomum burmannii extraction Cinnamon bark quills (Materia Medica, East Java, Indonesia) were cleansed and pulverized. Cinnamomum burmannii extraction using ethanol 96% as solvent was carried out in accordance with previous research.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Study revealed the cognitive enhancing and antioxidant property of HA-CA against streptozotocin (STZ) induced cognitive impairments and oxidative stress in rat model of Alzheimer disease (33). Evidenced showed that HA-CA increase body length in rotenone induced zebrafish larvae via the modulation of its antioxidant potential (34). Similarly, Janine et al, reported that HA-CA decrease ROS production, increase resistance to osmotic stress, increase life span, and heat stress due to its antioxidant potential in Chaenorhabditis elegans wild-type and knockout mutant (35).…”
mentioning
confidence: 99%